The Effect of the Dow Jones Industrial Average and the Shanghai Stock Exchange on the IDX Composite - Amanda, Devita Rezkia; Faizah, Iva; Yunarti, Yuyun (Universitas Islam Negeri Raden Intan, 2026)
The relationship between the Dow Jones Industrial Average and the Shanghai Stock Exchange Index to the IDX Composite is the main focus of this study. As an open market, the performance of the IDX Composite is influenced by several factors, particularly the trade war between the United States and China, the two largest economies in the world, which has been ongoing since early 2018. Using secondary data in the form of monthly closing prices of the Dow Jones Industrial Average, the Shanghai Stock Exchange, and the IDX Composite from 2018 to 2024, this study uses a quantitative approach. Multiple linear regression analysis is used to examine the extent to which the Dow Jones Industrial Average and the Shanghai Stock Exchange influence the IDX Composite. The results of this study are expected to provide a deeper understanding of how the Indonesian capital market interacts with the global stock market. The findings indicate that, partially, the Dow Jones Industrial Average has a significant positive influence on the IDX Composite during the 2018–2024 period, while the Shanghai Stock Exchange has a significant negative influence on the IDX Composite. Simultaneously, the Dow Jones Industrial Average and the Shanghai Stock Exchange have a significant influence on the IDX Composite during the same period. Keywords: DJIA, IDX COMPOSITE, SSE, Global Stock Market, Economic Growth.